Early and midterm outcomes after transaxillar versus transfemoral TAVI. data from the spanish TAVI registry. (25th November 2020) - Jimenez-Quevedo, P; Urbano Carrillo, C; Vaquerizo, B; Arzamendi, D; Artaiz, M; Perez-Moreiras, I; Moreu, J; Diaz, J; Blanco-Mata, R; Albarran, A; Cruz-Gonzalez, I; Baz, J.A; et al.
Abstract: : Transaxillary access (TAx) has emerged as a less invasive alternative access when transfemoral access (TF) is not possible in patients undergoing TAVI. The primary endpoint of this study was to compare total in-hospital and 30-day mortality of patients included in the Spanish TAVI registry that were treated by TAx versus TF access. Methods: All patients included in the Spanish TAVI registry who were treated by TAx or TF access were analyzed. In-hospital and 30-days outcomes were assessed using the Valve Academic Research Consortium definitions. An analyses by propensity score matching and multilevel logistic regression was performed for comparing both groups. Results: A total of 6603 patients were included, of whom 191 (2.9%) were treated by TAx and 6412 were treated with TF access. After the adjustment, the device success was similar between both groups (94%, TAx vs 95%, TF p=0.95) as well as the rate of vascular complications (11.9% Tax vs 11.9 TF; p=0.78), bleeding (7.7% TAx vs. 7.9% TF; p=0.62) and stroke (4.2% TAx vs. 2.0 TF; p=0.09). However, in-hospital and 30-day mortality was significantly higher in TAx access group versus TF 2.19 (1.13–4.26): p=0.02 and 2.11 (1.08–4, 13); P=0.02, respectively. Similarly, the rate of acute myocardial infarction 5.05 (1.94–13.1); p=0.001, renal complications 2.07 (1.19–3.60; p =) 0.01 and pacemaker implantation 1.56 (1.01–2.40); p=0.04 was higher in the TAx group versus TF. Conclusions: Transaxillary access compared to transfemoral access is associated with an increase in total in-hospital and 30-day mortality, as a result TAx access should be considered only in those cases in which TF is not possible Funding Acknowledgement: Type of funding source: None